Teaching emergency medicine residents health equity through simulation immersion. (29th September 2021) - Ward‐Gaines, Jacqueline; Buchanan, Jennie A.; Angerhofer, Christy; McCormick, Taylor; Broadfoot, Kirsten J.; Basha, Elshimaa; Blake, Jocelyn; Jones, Brena; Sungar, W. Gannon
Abstract: Objective: Our aim was to conduct a large, case‐based diversity, equity, and inclusion (DEI) simulation exercise with a goal to improve the DEI pillars of cultural and structural awareness for residents. Methods: Utilizing data resulting in poor health outcomes, the top eight themes were utilized, and via a modified Delphi approach, a diverse group of faculty developed representative cases. A mass simulation effort was organized with the assistance of our local simulation office. Twenty residents in groups of two to three rotated through all scenarios. Each resident group was allotted 15 min for each scenario. After each case, resident teams received feedback from standardized patients and a debrief together with the simulation directors. Pre‐ and postsimulation surveys were developed and distributed to residents. Results: Twenty residents completed the simulation. Eighteen completed a pre‐ and postsimulation survey. Every resident rated the overall usefulness of this activity as a 5.0 on a scale of 1 to 5 with 5 being the highest score. All cases demonstrated an improvement in the residents perceived confidence on a 9‐point Likert scale. All residents reported improved understanding of key concepts in health care disparities as related to race/ethnicity, homelessness, LGBTQIA, and their own biases. The largest improvement was seen in the overarching theme of "difficult conversations" with a presimulation survey mean of 3.9 and postsimulation survey mean of 6.5 (delta = +2.6, 95% confidence interval = 1.9 to 3.3, p  < 0.01). Conclusions: Emergency medicine residency programs must fulfill their obligation to DEI efforts and national requirements while ensuring competency clinically. Mass simulation exercises are a way to incorporate this training. This preliminary data shows promise for a solution and can be easily duplicated. Diversity, health equity, inclusivity, and cultural humility can be effectively taught by an innovative mass simulation effort.